Challenges and Prospects of the Deputy Attorney General for Military Criminal Affairs in the Handling of Military-Civilian Connectivity Cases - Al Syifa Rachman (The Prosecutor Law Review, 2025)
This study aims to analyze the execution of duties and authorities of the Deputy Attorney General for Military Criminal Affairs in handling koneksitas cases, with the objective of identifying the challenges encountered in its implementation and formulating future prospects for the Deputy Attorney General’s role. The research adopts a normative-empirical legal method, which is analyzed qualitatively and presented descriptively. The findings reveal that the Deputy Attorney General for Military Criminal Affairs has handled several koneksitas cases and contributed to the elimination of legal disparity. Nevertheless, certain issues remain concerning legal structure, substantive law, and legal culture. The future prospects for the Deputy Attorney General in handling koneksitas cases include ensuring proceedings that are simple, expeditious, and cost-effective, drafting technical guidelines, and fostering a unified understanding among law enforcement institutions.